Annexin A2 as a differential diagnostic marker of hepatocellular tumors - Longerich, Thomas; Haller, Maria Theresia; Mogler, Carolin; Aulmann, Sebastian; Lohmann, Volker; Schirmacher, Peter; Brand, Karsten (Pathology, research and practice, 2011)
While improved imaging techniques have made it possible to detect focal liver lesions smaller than 1cm in diameter, differentiating benign lesions from hepatocellular carcinoma (HCC) still remains a challenge. To address this problem and obtain a definite diagnosis, needle core biopsies are often performed, leading to an increased need for supportive ancillary techniques in the histopathological assessment of highly differentiated hepatocellular tumors. Here we evaluate the diagnostic value of immunohistologically detected Annexin A2 (ANXA2) expression in highly differentiated liver tumors. ANXA2 is a calcium-dependent phospholipid-binding protein that has been linked to malignant transformation and HCC development. Our data show that adding sinusoidal ANXA2 expression to the already established marker panel (GPC3, GS, and HSP70) increases the accuracy for the detection of well-differentiated HCC (74% sensitivity, 100% specificity). In addition, in our series, the combinations ANXA2-GPC3 and ANXA2-GS performed better compared to the other established marker combinations. In conclusion, we suggest that adding ANXA2 to the established diagnostic marker panel increases the reliability and objectivity of HCC diagnosis in liver biopsies.